Evaluation of zeolitized and vitreous tuffs located in the province of Holguín for use as a natural pozzolan in construction - Yunier Pérez-Rodríguez (Ciencia & Futuro, 2011)
This work involves the evaluation of vitreous and zeolitized tuff present in the ore bodies of Sagua de Tánamo, Guaramanao, Caimanes and San Andrés, based on chemical and granulometric characterizations and flexotraction and compression resistance of mortar made with 15 percent tuffaceous material as a substitute for Portland cement by applying the methods described in the standards for those specifications for its potential use as a natural pozzolan in construction applications